2019
DOI: 10.3390/jcm8101606
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Polycystic Ovary Syndrome: An Overview of Candidate Gene Systematic Reviews and Genome-Wide Association Studies

Abstract: Polycystic Ovary Syndrome (PCOS) is a complex condition with mechanisms likely to involve the interaction between genetics and lifestyle. Familial clustering of PCOS symptoms is well documented, providing evidence for a genetic contribution to the condition. This overview aims firstly to systematically summarise the current literature surrounding genetics and PCOS, and secondly, to assess the methodological quality of current systematic reviews and identify limitations. Four databases were searched to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 86 publications
(211 reference statements)
0
60
0
6
Order By: Relevance
“…A misconception was linked up with GWAS is that they document the precise genes; but in certainty, it documents the associated marker in the ethnic population ( Hiam et al, 2019 ). GWAS has been carried out in Han Chinese and European ancestry women and reproduced identifying 16 loci ( Chen et al, 2011 , Shi et al, 2012 , Hayes et al, 2015 , Day et al, 2015 ).…”
Section: Genetics Of Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…A misconception was linked up with GWAS is that they document the precise genes; but in certainty, it documents the associated marker in the ethnic population ( Hiam et al, 2019 ). GWAS has been carried out in Han Chinese and European ancestry women and reproduced identifying 16 loci ( Chen et al, 2011 , Shi et al, 2012 , Hayes et al, 2015 , Day et al, 2015 ).…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…2014 ). PCOS is intensified with obesity and along with significant reproductive, metabolic and psychological features; incorporating T2D ( Hiam et al, 2019 ). In 1921, Achard et al ( Achard, 1921 ) observed the beard women with diabetes and from then T2D has been linked up with PCOS ( Achard, 1921 ).…”
Section: Connection Between Pcos and T2dmentioning
confidence: 99%
“…Hence, it was unsurprising that PPP2R5C was found to cause human overgrowth, and to couple hepatic glucose and lipid homeostasis (Cheng et al 2015;Loveday et al 2015). It is also noteworthy that another ROH hotspot found on chromosome 5 (50-70 Mb) in this study is a homology segment of human RAB5B region on chromosome 12, which is a candidate locus for PCOS (Shi et al 2012;McAllister et al 2015;Sun et al 2016;Hiam et al 2019). RPS26, a ribosomal protein-encoding gene located at ROH5, was also a susceptibility gene for PCOS where the decreasing protein levels of oocyte-derived bone morphogenetic protein 15 (BMP15) and growth differentiation factor 9 (GDF9) contributed to arrested oocyte growth and premature ovarian failure in oocyte-specific Rps26 KO mouse (Liu et al 2018).…”
Section: Discussionmentioning
confidence: 69%
“…This is the case, for instance, for LHCGR, FSHR and FSHB genes related to hormonal alterations in PCOS or that of INSR and HMGA2 involved in metabolic feature of PCOS (27). A recent study reviewed these loci together with those found by narrative gene candidate approaches (28) and Table 2 indicated some of the most significant SNVs identified by GWAS in PCOS with clinical implications.…”
Section: Genes From Gwas Of Pcosmentioning
confidence: 99%